The menstrual cycle affects rectal sensitivity in patients with irritable bowel syndrome but not healthy volunteers - Houghton, L A (Copyright 2002 by Gut, 2002)
Background: We have previously shown that the menstrual cycle has no effect on rectal sensitivity of normal healthy women, despite them having looser stools at the time of menses. Patients with irritable bowel syndrome (IBS) often report significant exacerbation of their IBS symptoms with menses, raising the possibility that IBS patients may respond differently to the menstrual cycle. Aim and methods: Rectal responses to balloon distension during days 1–4 (menses), 8–10 (follicular phase), 18–20 (luteal phase), and 24–28 (premenstrual phase) of the menstrual cycle were assessed in 29 female IBS patients (aged 21–44 years), diagnosed by the Rome I criteria. During the course of the study patients completed symptom diaries to assess abdominal pain and bloating (visual analogue scale), and frequency and consistency of bowel habits. In addition, levels of anxiety and depression were assessed using the hospital anxiety and depression questionnaire. Results: Menses was associated with a worsening of abdominal pain and bloating compared with most other phases of the menstrual cycle (p<0.05). Bowel habits also became more frequent (p<0.05) and patients tended to have a lower general well being. Rectal sensitivity increased at menses compared with all other phases of the cycle (p<0.05). There was no associated change in rectal compliance, wall tension, or motility index. Neither was there any difference in resting anal pressure or the distension volumes required to relax the internal anal sphincter during the menstrual cycle. Conclusion: These data (1) confirm that IBS symptomatology is exacerbated at menses and (2) show for the first time that in contrast with healthy women, rectal sensitivity changes with the menstrual cycle. These cyclical changes in sensitivity suggest that women with IBS respond differently to fluctuations in their sex hormonal environment or its consequences compared with healthy females.